Possible roles of mitochondrial biogenesis in aging - de Grey, Aubrey (Henry Stewart Talks, 2007)
Oxidative phosphorylation, The mitochondrial DNA, Aging as the accumulation of damage, Types of aging damage, Types of damaged cells, Survival of cells lacking oxidative phosphorylation, The plasma membrane redox system, Reductive hotspot hypothesis, "Survival of the slowest" hypothesis, Allotopic expression, Hydrophobicity prevents allotopic expression of mitochondrially-encoded proteins, Ways to make these proteins allotopically expressible
Reviewed at 2016/11/18